ABUSE, ELITISM AND ACCOUNTABILITY: CHALLENGES TO THE PHILIPPINE CHURCH - Abellanosa, Rhoderick John S. (Asian Horizons, 2020)
There is a need to broaden the analysis of abuse within the Catholic Church to include any excessive use or application of power, authority, and influence that would detriment, damage and demoralize its members. In this light, the paper offers to go deeper in the understanding of abuse as rooted in ecclesiastical elitism which is a more serious problem than clericalism. Elitism within the Church is concrete in the various forms of privilege and distinctions, rooted in traditionally held theologies, culturally reinforced beliefs, and repeated practices of fame and honour. Because of these, abuse is perpetuated, thus making possible the lack of transparency in terms of financial management and disregard for the rights of people working within the various ministries of the Church. Realistically, power and authority are part of any human system. Precisely why there is a need for the Church to balance its hierarchical authority, power, and influence with accountability in the various structures and aspects of its governance and pastoral activities. The experience of the Philippine Church is the case and context of this study.